PENERAPAN MODEL PEMBELAJARAN RADEC TERINTEGRASI DEEP LEARNING MATERI PETA KELAS V TERHADAP PEMAHAMAN KONSEP DITINJAU DARI MOTIVASI BELAJAR - Lailiyati; Muhamad Afandi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to describe the implementation of the RADEC learning model (Read, Answer, Discuss, Explain, Create) integrated with a deep learning approach in map learning for fifth-grade elementary students and to analyze students’ conceptual understanding in terms of their learning motivation. This study employed a descriptive qualitative approach with a case study design. The participants were 33 fifth-grade students of SD N Petompon 01. Data were collected through observation, conceptual understanding tests, learning motivation questionnaires, interviews, and documentation. Data validity was ensured through technique triangulation. The results show that the implementation of the RADEC learning model integrated with deep learning was carried out systematically through the stages of read, answer, discuss, explain, and create and was able to create an active, contextual, and meaningful learning process. Students’ conceptual understanding differed across levels of learning motivation, where students with high motivation demonstrated better conceptual understanding than those with moderate and low motivation. In addition, the RADEC learning model integrated with deep learning provided positive learning motivation indicators, such as participation, interest, confidence, and persistence during learning. Therefore, the RADEC learning model integrated with deep learning can be used as an alternative instructional strategy to facilitate students’ conceptual understanding and learning motivation in map learning at the elementary school level.